2021
DOI: 10.1136/bmjgh-2021-004959
|View full text |Cite
|
Sign up to set email alerts
|

Higher risk of death from COVID-19 in low-income and non-White populations of São Paulo, Brazil

Abstract: IntroductionLittle evidence exists on the differential health effects of COVID-19 on disadvantaged population groups. Here we characterise the differential risk of hospitalisation and death in São Paulo state, Brazil, and show how vulnerability to COVID-19 is shaped by socioeconomic inequalities.MethodsWe conducted a cross-sectional study using hospitalised severe acute respiratory infections notified from March to August 2020 in the Sistema de Monitoramento Inteligente de São Paulo database. We examined the r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 51 publications
6
51
2
14
Order By: Relevance
“…COVID-19 pandemic caused a significant number of deaths worldwide, but the prevalence of comorbidities [ 7 , 8 ], lower education levels, socioeconomic inequalities as the healthcare system inexperience to deal with the pandemic [ 9 , 10 ] contributed to the increase of COVID-19 cases and deaths in low- and middle-income countries (LMICs) [ 11 13 ]. Most of these countries still show inadequate vaccination programs, lack of an accurate and rapid diagnosis as well as poor viral surveillance [ 10 , 14 16 ], contributing for the emergence of COVID-19 waves and new SARS-CoV-2 variants [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 pandemic caused a significant number of deaths worldwide, but the prevalence of comorbidities [ 7 , 8 ], lower education levels, socioeconomic inequalities as the healthcare system inexperience to deal with the pandemic [ 9 , 10 ] contributed to the increase of COVID-19 cases and deaths in low- and middle-income countries (LMICs) [ 11 13 ]. Most of these countries still show inadequate vaccination programs, lack of an accurate and rapid diagnosis as well as poor viral surveillance [ 10 , 14 16 ], contributing for the emergence of COVID-19 waves and new SARS-CoV-2 variants [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study using data aggregated at the country level from the 5 BRICS countries (Brazil, Russia, China, India and South Africa) showed that COVID-19 case numbers were associated with increasing levels of poverty 48 . Other studies have shown that COVID-19 mortality rates were greater in areas of Brazil with lower levels of various socio-economic indicators 49,50 . Possible explanations for the differences with our findings are that we focussed on the early stages of the local epidemic (time to arrival and early rate of propagation) and also that we were comparing trends between municipalities within one country.…”
Section: Discussionmentioning
confidence: 87%
“…We hypothesized that life satisfaction, happiness and quality of life would be lower during the COVID-19 pandemic than before the pandemic and that the evaluation would become worse from 2020 to 2021. We also expected to find interaction between the well-being evaluations and the respondents' family income, since there is higher risk of death from COVID-19 among the poorest (Li et al, 2021). The number of deaths in Brazil was one of the highest in the world.…”
Section: Research Questionsmentioning
confidence: 98%